SUSTAINABLE, ECOLOGIC AND GREEN ARCHITECTURE, TOWARDS INDONESIA SUSTAINABLE FUTURE - Ning Purnomohadi (Journal of Architecture&ENVIRONMENT, 2011)
The objectives, “Why Are We Becoming Green”? The first idea to greening the structural architecture building just recognized recently, why? Because there was a belief that the environmental enhancement efforts to combat its degraded environmental quality including “the green (building) is not our business, it is government business”. It is actually everybody business. In urban area, eighty percent of our activities are inside the building; at home, office, school, factory, hotel, gym, etc, only a small amount of the time spent outside the building, on the road or inside the car. Green is at the moment, a popular term in our daily life; a lot of companies and businesses claimed that they are green, by merely applying certain features in their properties. A lot of new property development claim that their development is “green”. Some Indonesian architects and engineers have been designing and applying the green principles in the design and achieve what supposed to be a green building standard. It is not merely a trend, it has to be a lifestyle change, the demand of the consumer of a “green” living environment meets the planet current conditions, climate change and degrading environmental conditions. The theoretical frame work is that it is timely and important to establish a Green Building Council. “Green” has become the shorthand term for the concept of sustainable development as applied to the building industry. Green buildings, including the appropriate site development as a sound landscape planning and design also known as high performance “buildings” in terms of i.e. materials efficient used, wise settings in the case of socio-economy-physical environment development as a whole, are intended to be environmentally responsible, economically profitable, and healthy places to live and work. If not, then all of us will be suffer caused by the negative environmental impacts. As human beings as part of the planet biological creature, we should be part and follow the natural law of the globe natural process.